Fostering professional competences in English: Partaking in dual degree programs - MATIYCHAK, ALIONA; Bezhenar, Iryna; Hladkoskok, Lesia (NGO European Scientific Platform, 2023)
The article surveys efficiency of dual degree programs that have English as one of their constituents. Modern research has proven these programs to be beneficial within such aspects as academic mobility, harmonization of European university degree systems, intensification of the European cooperation and integration processes, improving quality of profile education as well as language and cultural education. The present research methodology includes interviews with students and instructors, observation of classroom practices and surveys conducted within the period of February 2021 through January 2023. The main purpose of the research was to analyze tendencies in choice of major combinations for university dual degree programs, highlight the prerequisites and suggest ways for increasing efficiency of field-specific language education for students seeking dual degrees. The findings of the research illustrate that overall respondents’ needs and expectations have in focus professionally oriented language and translation training. Our theoretical contributions and practical implications present that the focus of language education must be shifted to personalized instruction that would promote language and translation training with maximum regard to professional needs within the area of the second specialism. We suggest implementation of competence-based, activity-based and task-specific approaches in teaching both languages and translation as they emphasize field-oriented interaction in the educational process and fit it in the context of authentic professional communication.
Keywords: language education; dual degree programme; student-oriented teaching strategies; profession-related English; translation practices for professional purposes